Controllable preparation of porous carbon and its application in blood purification
Patent Information
- Application Number
- CN202211449845.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-18
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-11-18
AI Technical Summary
其中,活性炭类吸附剂因具有价格低廉、应用范围广、解毒效果好等优点,在血液灌流中应用普遍,但却因材料的选择性吸附性能差等问题制约了它的应用和推广
[0038] This invention synthesizes microporous/mesoporous carbon precursors through a pore size pre-design strategy. After one-step carbonization, porous carbon materials with micropores or mesopores as the main components can be obtained quickly and easily. The synthesis method is simple and low in cost.
Smart Images

Figure CN118084909B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of blood purification technology, and more specifically, relates to the controllable preparation of porous carbon and its application in blood purification. Background Technology
[0002] Hemoperfusion technology utilizes an extracorporeal circulation perfusion adsorbent to draw blood from the patient's body and remove endotoxins and other harmful substances through adsorption. The core of hemoperfusion technology is the adsorbent material, which should be safe and non-toxic to the human body, non-allergenic, non-pyrogenic, chemically stable, not easily broken or detached, and have good blood compatibility. Currently, much research is focused on hemoperfusion adsorbent materials, and some materials have already been applied clinically, including activated carbon adsorbents, synthetic resin adsorbents, and immunosorbents. Among these, activated carbon adsorbents are widely used in hemoperfusion due to their low cost, wide application range, and good detoxification effect; however, their application and promotion are limited by poor selective adsorption performance. Although the market demand for activated carbon in medical perfusion devices in my country is huge, the industry is still in its early stages, underdeveloped, and relatively small in scale. Key technical issues such as the controllable preparation and structure-activity relationship of medical activated carbon urgently need to be addressed. Summary of the Invention
[0003] To address the aforementioned problems, this invention aims to provide a porous carbon material with controllable pore size and its preparation method. This porous carbon material is obtained by one-step carbonization of a carbon precursor with a pre-designed pore size structure, and can achieve highly selective adsorption of low-molecular-weight and medium-molecular-weight toxins in blood.
[0004] This invention provides a carbonaceous precursor, as shown in formula (I):
[0005]
[0006] According to the present invention, the pore size of the compound molecule of formula (I) is 1.8 nm.
[0007]
[0008] The present invention also provides a method for synthesizing the carbonaceous precursor shown in formula (I), comprising the following steps:
[0009]
[0010] The compound of formula (III) was reacted with the compound of formula (IV) in an organic solvent to obtain the carbonaceous precursor shown in formula (I).
[0011] According to the present invention, the molar ratio of the compound of formula (III) to the compound of formula (IV) is, for example, 2:1.
[0012] According to the present invention, the reaction temperature is, for example, 120°C to 180°C, such as 150°C or 180°C.
[0013] According to the present invention, the organic solvent is, for example, THF or DMF.
[0014] According to the present invention, the reaction time is, for example, 1 to 5 days, preferably 3 days.
[0015] The present invention also provides a carbonaceous precursor, as shown in formula (II):
[0016]
[0017] According to the present invention, the pore size of the compound molecule of formula (II) is 2.5 nm.
[0018]
[0019] The present invention also provides a method for synthesizing the carbonaceous precursor of formula (II) above, comprising the following steps:
[0020]
[0021] The compound of formula (III) was reacted with the compound of formula (V) in an organic solvent to obtain the carbonaceous precursor shown in formula (II).
[0022] According to the present invention, the molar ratio of the compound of formula (III) to the compound of formula (V) is, for example, 3:2.
[0023] According to the present invention, the reaction temperature is, for example, 120°C to 180°C, or, for example, 150°C to 180°C.
[0024] According to the present invention, the organic solvent is, for example, THF or DMF.
[0025] According to the present invention, the reaction time is, for example, 1 to 5 days, preferably 3 days.
[0026] The present invention further provides the use of the carbon precursor shown in formula (I) or the carbon precursor shown in formula (II) for the preparation of porous carbon materials.
[0027] The present invention also provides a porous carbon material, which is prepared from a carbon precursor shown in formula (I) or a carbon precursor shown in formula (II).
[0028] According to the present invention, the porous carbon material is obtained by carbonizing the carbon precursor in one step.
[0029] The present invention also provides a method for preparing porous carbon materials, comprising carbonizing the carbon precursor shown in formula (I) or the carbon precursor shown in formula (II) at high temperature to obtain the corresponding porous carbon material.
[0030] According to the present invention, the carbonization temperature is, for example, 400°C to 600°C, preferably 500°C.
[0031] According to the present invention, the reaction time of the carbonization step is, for example, 1 to 3 hours, preferably 1 hour.
[0032] The porous carbon materials described in this invention all have a specific surface area greater than 1000 m². 2 The sample size is 1.92 nm, meeting the required specifications. Furthermore, the pore size distribution of the samples is relatively concentrated, with the microporous carbon material prepared from the carbon precursor shown in Formula (I) having a pore size of 1.92 nm, and the mesoporous carbon material prepared from the carbon precursor shown in Formula (II) having a pore size of 2.81 nm. This demonstrates that porous carbon materials with uniform pore structure can be obtained through pre-designed pore structures.
[0033] The porous carbon material described in this invention exhibits highly selective adsorption of low molecular weight toxins (e.g., creatinine) and medium molecular weight toxins (e.g., vitamin B12) in the blood. The adsorption capacity is greater than 70%. The adsorption performance of the mesoporous material is slightly higher than that of the microporous material.
[0034] The present invention also provides the use of the porous carbon material for blood purification.
[0035] According to the present invention, the porous carbon material is used to adsorb low molecular weight toxins (e.g., creatinine) and medium molecular weight toxins (e.g., vitamin B12) in the blood.
[0036] The present invention also provides a disposable blood perfusion device comprising the porous carbon material described herein.
[0037] Beneficial effects
[0038] This invention synthesizes microporous / mesoporous carbon precursors through a pore size pre-design strategy. After one-step carbonization, porous carbon materials with micropores or mesopores as the main components can be obtained quickly and easily. The synthesis method is simple and low in cost.
[0039] The porous carbon material described in this invention has a large specific surface area, high porosity, low metal content, and exhibits highly selective adsorption of toxin molecules with a high adsorption capacity. Attached Figure Description
[0040] Figure 1 These are scanning electron microscope images of the microporous carbonaceous precursor of Example 1;
[0041] Figure 2This is a scanning electron microscope image of the mesoporous carbonaceous precursor of Example 2;
[0042] Figure 3 These are pore size distribution diagrams of the two microporous / mesoporous carbonaceous precursors in Examples 1 and 2;
[0043] Figure 4 These are creatinine adsorption effect diagrams of the two microporous / mesoporous carbonaceous precursors in Examples 1 and 2;
[0044] Figure 5 The graphs show the VB12 adsorption effects of the two microporous / mesoporous carbonaceous precursors in Examples 1 and 2. Detailed Implementation
[0045] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.
[0046] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.
[0047] Experimental reagents and equipment: 1,4,5,8-naphthalenetetracarboxylic anhydride (MTDA), N,N,N',N'-tetra(p-aminophenyl)p-phenylenediamine (TPDA), tris(4-aminophenyl)amine (TAPA), N,N-dimethylformamide (DMF), methanol, ethanol, hydrogen peroxide, vacuum drying oven, suction filtration device, magnetic stirrer, reaction vessel, rotary evaporator.
[0048] Example 1
[0049] Preparation of microporous carbonaceous precursors:
[0050] 28.4 mg MTDA and 23 mg TPDA (molar ratio 2:1) were added to the reactor, along with 5 ml DMF as the reaction solvent. The reactor was placed on a heating device and stirred, and reacted at 180°C for three days. The product obtained from the reaction was filtered and washed three times each with DMF and methanol. It was then placed in a reaction vessel and exchanged with methanol three times. After drying, a microporous carbon precursor was obtained. This precursor was then carbonized in one step at 500°C for 1 hour under normal pressure to obtain the microporous carbon material.
[0051]
[0052] The specific surface area of this microporous carbon material was determined to be 1034.33 m² using scanning electron microscopy. 2 / g, with an average pore volume of 0.84cm³. 2 / g, with an average pore size of 1.92nm.
[0053] Observation of scanning electron microscopy images shows that the microporous material has a uniform pore size distribution and a large specific surface area. This demonstrates that the present invention enables the controllable preparation of finely structured activated carbon with high specific surface area.
[0054] The microporous carbonaceous material was subjected to ICP testing, and the results are shown below.
[0055]
[0056] ICP test data for this microporous carbon material indicates that it contains extremely low levels of metals, far below the metal content requirements set by the National Medical Products Administration for disposable blood perfusion devices.
[0057] Creatinine adsorption tests were performed on the microporous carbon material, and the results showed that the microporous carbon material adsorbed up to 86% of the creatinine. The adsorption results are as follows: Figure 4 As shown.
[0058] The adsorption of VB12 on this microporous carbon material was tested, and the results showed that the microporous carbon material could achieve an adsorption capacity of 82% for VB12. The adsorption results are as follows: Figure 5 As shown.
[0059] Example 2:
[0060] 28.4 mg MTDA and 21.2 mg TAPA (molar ratio 3:2) were added to the reactor, along with 5 ml DMF as the reaction solvent. The reactor was placed on a heating device and stirred, and reacted at 180°C for three days. The product obtained from the reaction was filtered and washed three times each with DMF and methanol. It was then placed in a reaction vessel and exchanged with methanol three times. After drying, a mesoporous carbon precursor was obtained. This precursor was then carbonized in one step at 500°C for 1 hour under normal pressure to obtain the mesoporous carbon material.
[0061]
[0062] The specific surface area of the mesoporous carbon material was determined to be 1108.25 m² using scanning electron microscopy. 2 / g, with an average pore volume of 1.17cm³. 2 / g, with an average pore size of 2.81nm.
[0063] ICP testing was performed on the mesoporous carbonaceous material, and the results are shown below.
[0064]
[0065] ICP testing of the mesoporous carbon material showed that it also contained extremely low levels of metal, far below the requirements of the National Medical Products Administration for the amount of metal adsorption in disposable blood perfusion devices.
[0066] Adsorption tests on mesoporous carbon materials for creatinine (a metabolite in vivo) showed that the materials exhibited higher adsorption capacity, reaching 92%. The adsorption results are as follows: Figure 4 As shown.
[0067] Adsorption tests were performed on mesoporous carbon materials for VB12 (representing medium molecular weight substances). The results showed that the mesoporous carbon materials could achieve an adsorption capacity of 87% for VB12. The adsorption results are as follows: Figure 5 As shown.
[0068] Example 3:
[0069] 28.4 mg MTDA and 23 mg TPDA (molar ratio 2:1) were added to the reactor, along with 5 ml DMF as the reaction solvent. The reactor was placed on a heating device and stirred at 150°C for three days. The product obtained from the reaction was filtered and washed three times each with DMF and methanol. It was then placed in a reaction vessel and exchanged with methanol three times. After drying, a microporous carbon precursor was obtained. This precursor was then carbonized in one step at 500°C for 1 hour under normal pressure to obtain the microporous carbon material.
[0070] 28.4 mg MTDA and 21.2 mg TAPA (molar ratio 3:2) were added to the reactor, along with 5 ml DMF as the reaction solvent. The reactor was placed on a heating device and stirred at 150°C for three days. The product obtained from the reaction was filtered and washed three times each with DMF and methanol. It was then placed in a reaction vessel and exchanged with methanol three times. After drying, a mesoporous carbon precursor was obtained. This precursor was then carbonized in one step at 500°C for 1 hour under normal pressure to obtain the mesoporous carbon material.
[0071] ICP testing was performed on the microporous / mesoporous carbonaceous materials. The total content of barium, chromium, copper, lead, and tin in the microporous carbon was 0.0121 mg / L, and the cadmium content was 0.0005 mg / L. The total content of barium, chromium, copper, lead, and tin in the mesoporous carbon was 0.0131 mg / L, and the cadmium content was 0.0007 mg / L.
[0072] The adsorption performance of these two carbon materials for medium and low molecular weight substances was tested. The microporous carbon showed an adsorption capacity of 79% for creatinine (representing low molecular weight), while the mesoporous carbon showed 85%. The microporous carbon material showed an adsorption capacity of 72% for VB12 (representing medium molecular weight), while the mesoporous carbon showed 81%.
[0073] Example 4:
[0074] 28.4 mg MTDA and 23 mg TPDA (molar ratio 2:1) were added to the reactor, along with 5 ml of DMF as a reaction solvent. The reactor was placed on a heating device and stirred, and reacted at 180°C for three days. The product obtained from the reaction was filtered and washed three times each with DMF and methanol. It was then placed in a reaction vessel and exchanged with methanol three times. After drying, a microporous carbon precursor was obtained. This precursor was then carbonized in one step at 600°C for 1 hour under normal pressure to obtain the microporous carbon material.
[0075] 28.4 mg MTDA and 21.2 mg TAPA (molar ratio 3:2) were added to a reactor, along with 5 ml DMF as the reaction solvent. The reactor was placed on a heating device and stirred at 180°C for three days. The product was filtered and washed three times each with DMF and methanol. It was then placed in a reaction vessel and exchanged with methanol three times. After drying, a mesoporous carbon precursor was obtained. This precursor was then carbonized in one step at 600°C for 1 hour under normal pressure to obtain the mesoporous carbon material.
[0076] ICP testing was performed on the microporous / mesoporous carbonaceous materials. The microporous carbon absorption results showed that the total amount of barium, chromium, copper, lead, and tin was 0.0129 mg / L, and the cadmium content was 0.0011 mg / L. The mesoporous carbon absorption results showed that the total amount of barium, chromium, copper, lead, and tin was 0.0136 mg / L, and the cadmium content was 0.0009 mg / L.
[0077] The adsorption performance of these two carbon materials on medium and low molecular weight substances was tested. The microporous carbon showed an adsorption capacity of 75% for creatinine (representing low molecular weight), while the mesoporous carbon showed 85%. The microporous carbon material showed an adsorption capacity of 76% for VB12 (representing medium molecular weight), while the mesoporous carbon showed 83%.
[0078] Example 5:
[0079] 28.4 mg MTDA and 23 mg TPDA (molar ratio 2:1) were added to the reactor, along with 5 ml DMF as the reaction solvent. The reactor was placed on a heating device and stirred, and reacted at 180°C for three days. The product obtained from the reaction was filtered and washed three times each with DMF and methanol. It was then placed in a reaction vessel and exchanged with methanol three times. After drying, a microporous carbon precursor was obtained. This precursor was then carbonized in one step at 400°C for 1 hour under normal pressure to obtain the microporous carbon material.
[0080] 28.4 mg MTDA and 21.2 mg TAPA (molar ratio 3:2) were added to the reactor, along with 5 ml DMF as the reaction solvent. The reactor was placed on a heating device and stirred, and reacted at 180°C for three days. The product obtained from the reaction was filtered and washed three times each with DMF and methanol. It was then placed in a reaction vessel and exchanged with methanol three times. After drying, a mesoporous carbon precursor was obtained. This precursor was then carbonized in one step at 400°C for 1 hour under normal pressure to obtain the mesoporous carbon material.
[0081] ICP testing was performed on the microporous / mesoporous carbonaceous materials. The microporous carbon absorption results showed that the total amount of barium, chromium, copper, lead, and tin was 0.0136 mg / L, and the cadmium content was 0.0013 mg / L. The mesoporous carbon absorption results showed that the total amount of barium, chromium, copper, lead, and tin was 0.0139 mg / L, and the cadmium content was 0.0008 mg / L.
[0082] The adsorption performance of these two carbon materials on medium and low molecular weight substances was tested. The microporous carbon adsorbed 77% of creatinine (representing low molecular weight) while the mesoporous carbon adsorbed 79%. The microporous carbon adsorbed 72% of VB12 (representing medium molecular weight) while the mesoporous carbon adsorbed 75%.
[0083] Example 6:
[0084] 28.4 mg MTDA and 23 mg TPDA (molar ratio 2:1) were added to the reactor, along with 5 ml DMF as the reaction solvent. The reactor was placed on a heating device and stirred, and reacted at 180°C for three days. The product obtained from the reaction was filtered and washed three times each with DMF and methanol. It was then placed in a reaction vessel and exchanged with methanol three times. After drying, a microporous carbon precursor was obtained. This precursor was then carbonized in one step at 500°C for 2 hours under normal pressure to obtain the microporous carbon material.
[0085] 28.4 mg MTDA and 21.2 mg TAPA (molar ratio 3:2) were added to the reactor, along with 5 ml DMF as the reaction solvent. The reactor was placed on a heating device and stirred, and reacted at 180°C for three days. The product obtained from the reaction was filtered and washed three times each with DMF and methanol. It was then placed in a reaction vessel and exchanged with methanol three times. After drying, a mesoporous carbon precursor was obtained. This precursor was then carbonized in one step at 500°C for 2 hours under normal pressure to obtain the mesoporous carbon material.
[0086] ICP testing was performed on the microporous / mesoporous carbonaceous materials. The microporous carbon absorption results showed that the total amount of barium, chromium, copper, lead, and tin was 0.0131 mg / L, and the cadmium content was 0.0009 mg / L. The mesoporous carbon absorption results showed that the total amount of barium, chromium, copper, lead, and tin was 0.0135 mg / L, and the cadmium content was 0.0013 mg / L.
[0087] The adsorption performance of these two carbon materials on medium and low molecular weight substances was tested. The microporous carbon showed an adsorption capacity of 78% for creatinine (representing low molecular weight), while the mesoporous carbon showed 82%. The microporous carbon material showed an adsorption capacity of 73% for VB12 (representing medium molecular weight), while the mesoporous carbon showed 76%.
Claims
1. A porous carbon material, wherein, The carbon material is obtained by one-step carbonization of the microporous carbon precursor shown in Formula (I) or the mesoporous carbon precursor shown in Formula (II); the carbonization temperature is 400℃~600℃; and the carbonization time is 1~3 hours. The preparation method of the microporous carbonaceous precursor shown in formula (I) includes the following steps: The compound of formula (III) was reacted with the compound of formula (IV) in an organic solvent to obtain the microporous carbonaceous precursor shown in formula (I); The method for preparing the mesoporous carbonaceous precursor shown in formula (II) includes the following steps: The compound of formula (III) was reacted with the compound of formula (V) in an organic solvent to obtain the mesoporous carbonaceous precursor shown in formula (II).
2. The porous carbon material according to claim 1, wherein, In the preparation method of the microporous carbon precursor, the reaction temperature is 120℃~180℃; the organic solvent is THF or DMF.
3. The porous carbon material according to claim 1, wherein, In the preparation method of the mesoporous carbonaceous precursor, the reaction temperature is 120℃~180℃; the organic solvent is THF or DMF.
4. The porous carbon material according to claim 1, wherein, The carbonization temperature is 500°C.
5. The method for preparing the porous carbon material according to any one of claims 1-4, wherein, The microporous carbon precursor shown in formula (I) or the mesoporous carbon precursor shown in formula (II) is subjected to high-temperature carbonization. The preparation method of the microporous carbonaceous precursor shown in formula (I) includes the following steps: The compound of formula (III) was reacted with the compound of formula (IV) in an organic solvent to obtain the microporous carbonaceous precursor shown in formula (I); The method for preparing the mesoporous carbonaceous precursor shown in formula (II) includes the following steps: The compound of formula (III) was reacted with the compound of formula (V) in an organic solvent to obtain the mesoporous carbonaceous precursor shown in formula (II). The carbonization temperature is 400℃~600℃; the carbonization time is 1~3 hours.
6. The method for preparing the porous carbon material according to claim 5, wherein, The carbonization temperature is 500°C.
7. A blood perfusion device comprising the porous carbon material according to any one of claims 1-4.
Citation Information
Patent Citations
Preparation method of porous carbon based on covalent organic framework materials and porous carbon material
CN107720720A
Polyimide covalent organic framework and preparation method and application thereof
CN110218317A